The Role of Government in Developing Coffee-based Agro-Industry: Case Study in Pagar Alam, South Sumatra - Syafitri, Wenda (JPAS (Journal of Public Administration Studies), 2016)
Coffee plantation has become a primary source of income for majority of populations in Pagar Alam. There are approximately 8,745 coffee farmers in this city, most of them are smallholders with average 1 ha of land. Since the globalization has influencing all of the aspects in the world, coffee agro-food system in Pagar Alam is not only involved the local farmers and farm workers who produce the coffee, but also the massive industry that processes, packages, and distributes the coffee to consumers. This research tried to describe the potential of coffee-based agro-industry in the role of creating value-added and increase local farmers’ income as well as to analyze some obstacles faced by local farmers in its implementation. This research used quantitative approach by using investment feasibility analysis combined with qualitative approach using interviews. There were 40 respondents involved in this research. The result concludes that coffee-based agro-industry is one of potential livelihoods for the smallholders in Pagar Alam. The investment feasibility analysis showed that processing coffee powder is more profitable than selling unprocessed coffee beans.